Sosialisasi Public Speaking Pada Pengelolaan Destinasi Wisata Dinas Pariwisata Provinsi Kepulauan Riau - Imam Ozali; Charles AN; Cecep Pahrudin (Jurnal Abdimas Transportasi & Logistik, 2022)
Public Speaking is very important and very much needed in communicating with the community. The purpose of this public speaking socialization is so that all those involved in developing tourist destinations, such as tourist villages, airlines, hotels and travel agents in the Riau Islands Province understand and know how to communicate properly and correctly to tourists visiting the Riau Islands Province. Several types of public speaking are informative public speaking, persuasive public speaking, entertaining public speaking, technical public speaking and short public speaking. The problem that we found in the tourism industry of the Riau Islands Province was a condition that the use of good and correct public speaking in the tourism industry had not been maximized. So that it has an impact on the poor service provided to tourists during their visit to the Riau Islands Province. The method we use in this Community Service (PKM), is that we collaborate with the Tourism and Culture Office of the Riau Islands Province to disseminate information to all those involved in developing tourist destinations, such as Tourism Villages, Airlines, Hotels and Travel Agents in the Riau Islands Province. The outcome we hope for with this Community Service (PKM) is a condition where all tourism actors in the Riau Islands Province can communicate with tourists in Bintan Regency through the use of good and correct public speaking. The end result is the occurrence of tourist satisfaction during their visit in the Riau Islands Province, which has an impact on the increasing number of tourist visits in the Riau Islands Province.